2018
DOI: 10.18865/ed.28.s1.253
|View full text |Cite
|
Sign up to set email alerts
|

The Intersectionality of Racial and Gender Discrimination among Teens Exposed to Dating Violence

Abstract: Strategies to prevent TDV in this population should not ignore the compounding negative effects of racial and gender discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Sexism is associated with violence in adolescent relationships, and it was found that, higher the levels of sexism in a culture, the greater is the likelihood of perpetrating violence (Dosil et al, 2020). Another intersectional perspective study linked violence in adolescent couples to gender discrimination in addition to teens being discriminated against for being of Latin American origin (Roberts et al, 2018). Likewise, the acceptance of violence and traditional behaviors in gender roles is associated with the perpetration of violence (Reyes et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sexism is associated with violence in adolescent relationships, and it was found that, higher the levels of sexism in a culture, the greater is the likelihood of perpetrating violence (Dosil et al, 2020). Another intersectional perspective study linked violence in adolescent couples to gender discrimination in addition to teens being discriminated against for being of Latin American origin (Roberts et al, 2018). Likewise, the acceptance of violence and traditional behaviors in gender roles is associated with the perpetration of violence (Reyes et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the observed DV associated factors in this study, worth noting is the greater probability of foreign-born girls and boys to experience dating violence, compared to the young population born in Spain. On the one hand, in interpreting this result, it is important to consider that the immigrant population may have different conceptualizations of love, and may be more tolerant of certain behaviours considered violent compared to the native-born population [ 32 , 33 ]. On the other hand, the immigrant population from low-income countries that migrates for economic reasons may be exposed to greater social and economic inequality than the native-born population [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Project Dream, Own, Tell (DOT) is a youth prevention program developed in partnership with youth from diverse, underrepresented groups (e.g., immigrants, racial/ethnic minoritized youth, and LGBTQ + , transgender and gender questioning youth) across New York City (NYC) (Sakar et al, 2021). Grounded in intersectionality theory (Collins, 2017) (that explores intersections between interlocking systems of oppression and violence) and work that highlights resistance and protective factors (Jones & Neblett, 2016;Roberts et al, 2018) as well as developmental asset theory (that focuses on youth strengths rather than just risk factors) (Atkiss et al, 2011), DOT creates a platform for youth to be leaders of social norms change in their communities. Through program components of healthy relationships education, peer and adult engagement, DOT prepares youth to change modifiable social processes that are part of RSV risk or may protect against it, by helping youth overcome the risk of collective disadvantage in their communities.…”
Section: Project Dream Own Tellmentioning
confidence: 99%